2019
DOI: 10.1091/mbc.e19-02-0086
|View full text |Cite
|
Sign up to set email alerts
|

Specialized eRpL22 paralogue-specific ribosomes regulate specific mRNA translation in spermatogenesis inDrosophila melanogaster

Abstract: The functional significance of ribosome heterogeneity in development and differentiation is relatively unexplored. We present the first in vivo evidence of ribosome heterogeneity playing a role in specific mRNA translation in a multicellular eukaryote. Eukaryotic-specific ribosomal protein paralogues eRpL22 and eRpL22-like are essential in development and required for sperm maturation and fertility in Drosophila. eRpL22 and eRpL22-like roles in spermatogenesis are not completely interchangeable. Flies depleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 76 publications
1
27
0
1
Order By: Relevance
“…The function of the RpL22 and RpL22-like paralog pair in Drosophila testis has been explored and it has been suggested that the two proteins are not functionally redundant in development or spermatogenesis. However, knockdown of RpL22 is partially rescued by RpL22-like and vice versa [34, 35]. Further work is needed to directly link effects on ribosome composition and mRNA translational output, as the two paralogs may interact with different pools of mRNA in the testis [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of the RpL22 and RpL22-like paralog pair in Drosophila testis has been explored and it has been suggested that the two proteins are not functionally redundant in development or spermatogenesis. However, knockdown of RpL22 is partially rescued by RpL22-like and vice versa [34, 35]. Further work is needed to directly link effects on ribosome composition and mRNA translational output, as the two paralogs may interact with different pools of mRNA in the testis [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, knockdown of RpL22 is partially rescued by RpL22-like and vice versa [34, 35]. Further work is needed to directly link effects on ribosome composition and mRNA translational output, as the two paralogs may interact with different pools of mRNA in the testis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression of eRpL22 along with eRpL22-like within eye tissue cell types is consistent with the hypothesis that eRpL22 and eRpL22-like have functionally distinct roles within these cells. These roles may include distinctive ribosome-related functions, including their assembly into specialized ribosomes (eg, 1,11,12,22 ) or roles that are independent of ribosomal processes (eg, reviewed by 9,35 ). We used IHC and confocal microscopy to assess eRpL22-like localization relative to other large subunit Rps, RpL9 and RpL23a or to the nucleolar marker fibrillarin.…”
Section: Ribosomal Roles Are Implicated For Erpl22-like In Eye Devementioning
confidence: 99%
“…In fact, we have recently demonstrated unique patterns of specific translation on eRpL22 ribosomes and eRpL22-like ribosomes in the germline. 22 A complete developmental eRpL22-like expression profile within the developing eye is necessary to understand functional contributions of this Rp to developmental and differentiation processes required to build an eye.…”
Section: Introductionmentioning
confidence: 99%
“…Brian McStay (National University of Ireland, Galway) described nucleolar formation and subsequent fusion in human cells from a chromosomal perspective. Using monochromosomal cell hybrids to engineer individual NOR 3 -bearing acrocentric chromosomes, he showed that their p-arms with fused proximal and distal junctions lacking intervening rDNA still associate with nucleoli. He also showed that individual NORs occupy distinct territories within large mature nucleoli.…”
Section: Rdna Dynamicsmentioning
confidence: 99%